Analysis of Disaster Risk Attitudes in Situation Awareness: A Cultural and Gender Perspective. (September 2016) - Helander, Martin G.; Khalid, Halimahtun M.
Most research on disaster use a social vulnerability approach. Social vulnerability to disaster is dynamic process that is rooted in culture, gender, ethnicity, age and other power relationships. This assumes that disasters are effects of human constructs due to their use of natural and built environments. Disaster risk is socially distributed in ways that reflect social divisions existing in society. Hence, our study investigated the effects of cultural groups and gender on risk attitudes for two types of disasters, namely natural and human-induced disasters. Risk attitude in this study is a summative of five components: risk identification, cognition, affect, trust and behavior. There were significant differences in risk attitudes between cultural groups, namely, Malaysian and Indonesian, and genders at three levels of situation awareness: perception, comprehension and projection. In addition, the study revealed utility of using attitudes and experience of disasters in psycho-cultural analysis of social vulnerabilities.